Podstawa wymiaru składek i świadczeń w koordynacji systemów zabezpieczenia społecznego - Dzienisiuk, Dorota (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
Coordination of social security schemes consists of connecting separate schemes introduced by respective states in order to protect migrant people. Bilateral and multilateral coordinating measures binding the Republic of Poland do not refer directly to the basis of calculating contributions. Periods of affiliation to social security, not the amount of contributions or bases for calculating contributions, are coordinated. Within the scope of benefits the aim is to provide the amount of benefits adequate to the situation of an individual. Thus, as a rule, actual remuneration, bases for calculating contributions or contributions relevant to the individual in the state granting the benefit are taken into consideration.
Keywords: social security; coordination; basis for calculating contributions